Healthy Eating: Understanding the Nutrition Facts Label - Linda Bobroff; Karla P. Shelnutt (EDIS)
The U.S. Food and Drug Administration (FDA) requires that most food packages have the Nutrition Facts label. This label contains information about nutrients in the food to help people make healthier food choices. Older adults can use the label to choose foods that provide required daily nutrients or fit with a diet plan to manage a disease or health condition. This 4-page fact sheet is a major revision that discusses the Nutrition Facts label, checking calories, limiting certain nutrients, % Daily Values, and consuming enough fiber, vitamin D, potassium, calcium, and iron.